The Effectiveness of Think-Pair-Share (TPS) Method on Teaching Writing Descriptive Text at Second Grade of Mts Ihyaul Ulum Manyar Sekaran Lamongan - salamun (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2025)
This research was conducted on second-grade students of MTs Ihyaul Ulum Manyar Lamongan. The researcher applies the think-pair-share method to determine the effect of the method on understanding the descriptive text. The research design is experimental research. The researcher applies preexperimental one group pre-test and post-test. The subject of the study was students? VIII B of MTs Ihyaul Ulum Manyar Lamongan. The technique of data collection is pre-test, treatment, and post-test. Meanwhile, the method of data analysis the researcher used a t-test. The result of this study indicates that the average obtained from the posttest was higher than the pre-test. This indicated that the treatment was successful. It has paired T-test calculation researcher. T-test was calculated to determine the comparison of the two means between pre-test and post-test. The result shows that the value of sig (2-tailed) is 0.000 at the critical value for the 5% level. This means that the significance value is less than 5% or (6,173 > 2,131). So, the null hypothesis can be rejected. It can be concluded that the think-pair-share method is effective.